2021
DOI: 10.3389/fenrg.2021.661850
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Biodegradation of 17β-Estradiol by Candida utilis CU-2 and Lactobacillus casei LC-1

Abstract: The release and fate of estrogens have attracted more and more public attention. Biodegradation is an important method for estrogen removal from the environment. However, few comparative studies concentrated on the degradation of 17β-estradiol (E2) by fungi and bacteria. In this study, the removal efficiencies of E2 by fungi (Candida utilis CU-2) and bacteria (Lactobacillus casei LC-1) were investigated through influencing factors, kinetics, and biodegradation pathways. The results demonstrated that both C. ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Zhang et al also reported that the addition of carbon sources seemed to inhibit the degradation of E2, and concluded that strain FJ1 preferred the use of additional carbon sources over E2 [ 11 ]. There is also evidence that the efficiency of degradation of pollutants by degrading bacteria is influenced by the concentration of added carbon sources [ 24 ]. In the future, the mechanism of E2 degradation by strain MZT7 needs to be further studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al also reported that the addition of carbon sources seemed to inhibit the degradation of E2, and concluded that strain FJ1 preferred the use of additional carbon sources over E2 [ 11 ]. There is also evidence that the efficiency of degradation of pollutants by degrading bacteria is influenced by the concentration of added carbon sources [ 24 ]. In the future, the mechanism of E2 degradation by strain MZT7 needs to be further studied.…”
Section: Resultsmentioning
confidence: 99%
“…At a retention time of 13.07 min, the substance P1 was identified as estrone (E1). In almost all studies on microbial degradation of E2, E1 has been detected as an intermediate metabolite [ 14 , 17 , 19 , 20 , 24 , 42 ], and it is the main degradation product of E2 [ 2 , 4 ]. Moreover, many studies suggest that microbial degradation of E2 begins first with the D-ring, where the hydroxyl group at C-17 is oxidized to a ketone group and E2 is converted to E1 [ 25 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon backbone of steroids consists of four fused rings (named A to D) carrying different side substitutions (alcohol, ketone groups and carbon chains of up to ten carbon atoms). The oxidation of the steroid core and the degradation of side chains according to the fatty acid oxidation pathway are key reactions for their microbial degradation [ 54 , 55 ]. Although all our L. salivarius strains harbor seven genes encoding enzymes participating in estrogen metabolism, their capacity to degrade E2 differed significantly, suggesting that they may exhibit different regulatory pathways, as previously reported [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although substrate specificity is variable among them, these works suggest that, under substrate induction, different enzymes of this family can catalyze the conversion of E2 into E1, although in our case, to a lesser extent. Other degradation pathways of E2 that do not involve the initial conversion into E1 have been proposed for Lactobacillus casei LC-1, although the exact mechanisms have not been elucidated yet [ 55 ]. It should be highlighted that estrogen-degrading mechanisms have been widely studied in microorganisms isolated from soil, sewage and water, where the concentration of environmental estrogens may be relatively high [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%